Can FDI and ODI two-way flows improve the quality of economic growth? Empirical Evidence from China. Issue 44 (20th September 2021) - Luo, Sumei; Shi, Yixiang; Sun, Yongkun; Zhao, Zhiqi; Zhou, Guangyou
ABSTRACT: Different from the existing literature which only studied the unilateral impact of the FDI or the ODI on economic growth, this paper took both the FDI and the ODI into the analysis framework of international capital flow on economic growth, and tried to introduce the mediating effect model to test the transmission mechanism and influence effect of international capital two-way flow on the economic growth. The results showed that both the FDI and the ODI can significantly improve the quality of economic growth, and the role of the FDI was stronger than that of the ODI. At the same time, the FDI and the ODI had obvious regional heterogeneity in promoting the quality of economic growth. International capital flow mainly requires three mediating effects to improve the quality of economic growth, which are the employment, the technology spillover as well as the output efficiency. The three effects of the FDI have a played significant role in promoting the quality of economic growth, while the ODI mainly plays a role through the improvement of output efficiency and technology reverse spillover. There are also significant regional differences in mediating effects.